Estilos de vida, corpo e saúde : usos e apropriações pelas leitoras da revista Women´s Health Brasil - Almeida, Ludmila dos Santos (2015)
This study is qualitative and aims to analyze how readers receive the information they find with the women's magazine reading Women's Health Brazil, with regard to healthy lifestyle, body and health. To analyze the reception of the contents of this magazine were interviewed 6 readers and is used as a methodological strategy for interpreting the content of these interviews thematic analysis (Bardin, 2006), as well as a theoretical dialogue mainly based on the approaches of Zygmunt Bauman. The results demonstrate that the quest for a healthy lifestyle, nutrition and physical activity appear as the main care to achieve this goal. The reader is presented as an active subject and participant in the self improvement process, still able to reframe the information received adapting them to their needs. The magazine that process, presents itself as a counselor, giving tips and information that may or may not be followed by its readers